Auditoría de gestión y su incidencia con el cumplimiento de los planes y programas de la empresa pública municipal de agua potable y alcantarillado del cantón Pichincha, año 2014 - Mera Alcívar, Hilda Maira (2016)
The present Project of Investigation, was developed in the Municipal Public corporation of Drinking water and Sewer system of the Canton Pichincha, the same one that is located in the Neighborhood Bellavista, Via Blanket Quevedo; he/she had as main objective: To carry out an administration Audit to determine their incidence in the execution of the plans and programs of the Municipal Public corporation of Drinking water and Sewer system of the Canton Pichincha, year 2014. For the development of this project they were used the inductive Method to carry out the position of the problem of the investigation, the deductive method, the same one was also used that allowed to recognize the discoveries of the audit, once the different ones were applied technical and methodological procedures characteristic of an administration audit, what corroborated the realized asseverations. As fundamental part of the results it was obtained that the company has a training deficiency in the personnel that which doesn't allow the personnel to carry out his works with efficiency and speed and it allows to deploy the execution of the plans and programs settled down in the company, that which impedes an evaluation and pursuit of the same one. And to the execution of the objectives and goals that which the personnel's collaboration is needed that works in the company and this way to optimize the organizational structure. It is necessary to highlight that the officials ignore the mission, vision, plans and programs that it carries out the institution and this way to be able to collaborate in the application of a system to carry out the trainings to the personal one and an improvement is increased this way in the quality to the moment to carry out its work and this way to be able to fulfill the objectives that are focused to the quality and excellence when offering their services to the population of the Canton Pichincha. Keywords: Audit, management, plans, programs.